Improving Packaging Logistics System: A Study Case of Camembert Cheese - Mushonnifun Faiz Sugihartanto; Syarifa Hanoum; Nalaputi Basoeki; Elif Tiryakioglu; Cynthia Ferrier (JURNAL SOSIAL HUMANIORA (JSH), 2021)
cheese using the packaging evaluation method and to propose suggestions to improve the efficiency of packaging logistics that would impact the efficiency of the entire supply chain. We engage all supply chain actors for evaluating the packaging features. The first packaging is not convenient as its weight and cost are quite high for cheese, the secondary packaging is deemed less efficient, whilst the tertiary packaging is not optimal in terms of traceability. Speaking of cost, environmental impacts, especially impact on other features in the supply chain, we propose solutions to replace the circular wooden box of the cheese with a cardboard box with a round shape. Then, only the cardboard trays will be used as secondary packaging all along the supply chain. These combined solutions reduce the handling work, the packaging material cost and provide more convenience for all actors.